2018
DOI: 10.1016/j.jjie.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Do teaching practices matter for students’ academic achievement? A case of linguistic activity

Abstract: This paper analyzes the effects of teaching practices on the educational achievement of elementary school students. Using unique student-level test score data and controlling for school fixed effects, we estimate the impact of linguistic activity in the classroom on reading and mathematics test scores of sixth grade students. We find that linguistic activities improve students reading and mathematics test scores and that their impacts are substantial. We find heterogeneity in the effect of these activities acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Hojo (2012) and Hojo and Oshio (2013) found a positive association of female teachers with math test scores of 8 th grade students with TIMSS data from 2007. Tanaka and Ishizaki (2018) examined the effect of teaching practice of classroom teachers on test score of students in public primary schools. They found that teaching methods focusing on logical thinking had a positive impact on students' test score of both language arts and mathematics.…”
Section: Statesmentioning
confidence: 99%
“…Hojo (2012) and Hojo and Oshio (2013) found a positive association of female teachers with math test scores of 8 th grade students with TIMSS data from 2007. Tanaka and Ishizaki (2018) examined the effect of teaching practice of classroom teachers on test score of students in public primary schools. They found that teaching methods focusing on logical thinking had a positive impact on students' test score of both language arts and mathematics.…”
Section: Statesmentioning
confidence: 99%
“…Suradin et al, (2022) discovered that students' attitudes toward explicit and implicit grammar instruction approaches differ, with some favoring one over the other. Tanaka & Ishizaki (2018) discovered that linguistic activities in the classroom increased kids' reading and math exam scores, but the impact may vary depending on the learning environment. Ahmed (2013) discovered that students in Bangladesh fail to grasp grammatical competence, and he recommends creating dynamic and fascinating techniques to teach grammar in order to increase student performance.…”
Section: Future Directions and Possibilitiesmentioning
confidence: 99%
“…Recent studies have shown that some teaching practices substantially impact educational outcomes (Schwerdt and Wuppermann, 2011;Van Klaveren, 2011;Bietenbeck, 2014;Lavy, 2016;Tanaka and Ishizaki, 2018;Motegi and Oikawa, 2019). It is possible that differences in teachers' majors may cause differences in their knowledge and teaching practices, affecting students' academic achievement.…”
Section: Mechanismmentioning
confidence: 99%